Production of stress in hearing impaired children - Sarumathi K (Journal of All India Institute of Speech and Hearing, 1970)
Learning a language includes not only the segmental aspects but also the segmental aspects but also the suprasegmental aspects. The suprasegmental features are intonation, rhythm and stress. Stress is the comparative force with which the separate syllables of a sound group are pronounced. To put it in simpler terms, stress is the increased effort.